2016
DOI: 10.5937/sjm11-8062
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model: II for work-life balance of IT professionals in Chennai

Abstract: The study developed and tested a model of work life balance of IT professionals employing structural equation modeling (SEM) to analyze the relationship between work place support (WPS) and work interference with personal life (WIPL), personal life interference with work (PLIW), satisfaction with work-life balance (SWLB) and improved effectiveness at work (IEW). The model fit the data well and hypotheses are generally supported. WPS and SWLB are negatively related to WIPL and PLIW. However, there is a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Otherwise, when the workers contemplate a longer relationship with their employers, they do expect to have some WPS to enhance their WLB. Previous studies (Banu 2016;Jang 2009) also found that perceived WPS has a positive effect on WLB. Hence, to improve WLB of construction workers, emphasis should be placed on WPS, and organizations should put policies in place that would cultivate workers' trust in their employer.…”
Section: Structural Modelmentioning
confidence: 63%
“…Otherwise, when the workers contemplate a longer relationship with their employers, they do expect to have some WPS to enhance their WLB. Previous studies (Banu 2016;Jang 2009) also found that perceived WPS has a positive effect on WLB. Hence, to improve WLB of construction workers, emphasis should be placed on WPS, and organizations should put policies in place that would cultivate workers' trust in their employer.…”
Section: Structural Modelmentioning
confidence: 63%
“…Some leadership style studies apply SEM (Kim, 2014;Shrestha, 2012). Many other studies examined the effect of work-life balance on employee performance by using SEM models (Tavassoli & Sune, 2018;Banu, 2016;Haar et al, 2014). Another studies identified the relationship of employee engagement using SEM (Hanaysha, 2016;Anitha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on transformational leadership styles that have used SEM were also conducted by [48,49,55,56]. The study of work-life balance Modern Ship Engineering, Design and Operations also applies a lot of SEM models adapted by [57][58][59]. Meanwhile, other studies related to employee engagement that use SEM are described by [60,61].…”
Section: Methodsmentioning
confidence: 99%